Petrology and geochemistry of meta-ultramafic rocks in the Paleozoic Granjeno Schist, northeastern Mexico: Remnants of Pangaea ocean floor - Torres Sánchez, Sonia Alejandra; Augustsson, Carita; Jenchen, Uwe; Barboza Gudiño, José Rafael; Alemán Gallardo, Eduardo Alejandro; Ramírez Fernández, Juan Alonso; Torres Sánchez, Darío; Abratis, Michael (2017)
Abstract: The Granjeno Schist is a meta-volcanosedimentary upper Paleozoic complex in northeastern Mexico. We suggest different tectonic settings for metamorphism of its serpentinite and talc-bearing rocks based on petrographic and geochemical compositions. According to the REE ratios (LaN/YbN = 0.51–20.0 and LaN/SmN = 0.72–9.1) and the enrichment in the highly incompatible elements Cs (0.1 ppm), U (2.8 ppm), and Zr (60 ppm) as well as depletion in Ba (1 – 15 ppm), Sr (1–184ppm),Pb(0.1–14ppm),andCe(0.1–1.9ppm)the rocks have mid-ocean ridge and subduction zones characteristics.TheserpentinitecontainsAl-chromite,ferrian chromiteandmagnetite.TheAl-chromiteischaracterized byCr#of0.48to0.55suggestingaMORBorigin,andCr#of 0.93 to 1.00 for the ferrian chromite indicates a prograde metamorphism.Weproposeatleasttwoserpentinization stagesoflithosphericmantlefortheultramaficrockofthe GranjenoSchist,(1)afirstinanocean-floorenvironment atsub-greenschisttogreenschistfaciesconditionsand(2) later a serpentinization phase related to the progressive replacement of spinel by ferrian chromite and magnetite atgreenschisttolowamphibolitefaciesconditionsduring regional metamorphism. The second serpentinization phase took place in an active continental margin during the Pennsylvanian. We propose that the origin of the ultramaficrocksisrelated toanobductionandaccretional eventatthewesternmarginofPangea. Keywords: ultramafic rocks; serpentinite; Granjeno Schist;northeasternMexico,Gondwana,Pangea